Congenital Partial Absence of Pericardium: A Mimic of Arrhythmogenic Right Ventricular Cardiomyopathy. (10th April 2018) - Foo, J. S.; Koh, C. H.; Sahlén, A.; Tang, H. C.; Lim, C. P.
Abstract : Congenital absence of pericardium is a rare condition with electrocardiogram, chest X-ray, and echocardiographic findings which may mimic those of other cardiac conditions. We present a case of a 19-year-old asymptomatic female with incidental cardiomegaly on chest X-ray and electrocardiographic and echocardiographic changes, which meet the revised task force criteria for definite arrhythmogenic right ventricular cardiomyopathy but subsequently confirmed to have congenital partial absence of pericardium on cardiac magnetic resonance imaging.